DOPUSZCZALNOŚĆ OKAZANIA GŁOSU W ŚWIETLE AKTUALNEJ REGULACJI PRAWNEJ - Szczepaniec, Maria (Zeszyty Prawnicze, 2016)
ADMISSIBILITY OF THE PRESENTATION OF THE SPEECH IN LIGHT OF CURRENT LEGAL REGULATION Summary The article discusses the issues concerning the presentation of the speech. This issues is quite seldom discussed in the literature. The basic problem with the presentation of the speech concerns the legal basis to carry out this action. The article presents also the definition and the types of the presentation. Considerations are concentrated on giving of answer on question, if the presentation of the speech is admissible in light of current legal regulation.